Contemporary Ecological Paradigms and Emerging Challenges of Water Security Nexus for Pakistan - Asma Siddique (Journal of Political Studies, 2021)
Water Securitization is key hindrance to socio-economic and human development for a water-based economy. The trajectory relations among states, hydrological vulnerabilities, multi-faced water meagerness with crucial water sharing challenges are prompting geo-strategic and geo-political arduousness in South Asia. The chief intension of research is to elaborate the eminence of extreme water belligerences related with traditional state security concerns predominantly in case of Pakistan and India which are co-basin rival states of Indus Rivers System. Pakistan being single basin and lower riparian is profoundly reliant on Indus Basin (a lifeline for the country) due to its agrarian economy. The ever-increasing gap between demand and supply is instigating water scarceness, possessing numerous domestic aspects, political and climatic factors, Indian hydro-hegemonic intensions, etc. The ideology of water securitization along with national security is toxic in body politics, ensuing hydrological security complexes, security dilemmas and sufferer anxiety syndrome for Pakistan, elaborated by Securitization Theory paradigms. The research is based on descriptive and deductive reasoning approaches, mixed research methodology and utilization of secondary data resources. There is a dire need of dynamic responses, establishment of operative institutions, mutual cooperation at all levels, with de-securitization of riparian and hydrological security discourses can be valued, if not then it could intensify the human, national and hydro-security challenges for concerning states.